Parameter Penyelesaian Delik Adat Melalui Keadilan Restoratif Berdasarkan Kitab Undang-Undang Hukum Acara Pidana - Boydo Saragih (Universitas Sumatera Barat, 2026)
The enactment of the New Criminal Code (KUHP) materially acknowledges the existence of customary criminal law (living law), which aligns with the Restorative Justice mechanism in the New Criminal Procedure Code (KUHAP). However, the absence of objective material parameters within the criminal justice system leaves state law vulnerable to biased recognition of customary law, risking power imbalances, double jeopardy, and mob justice. This study aims to formulate a conceptual framework as a material boundary in examining the validity of customary offense settlements. Using a normative legal research method with statutory and conceptual approaches, this study proposes the doctrinal concept of the